Introduction to Rights-based Direct Practice with Children - Desai, Murli (Rights-based Direct Practice with Children,, 2018)
The Sourcebook introduces the theoretical and ideological foundation and methodological basis of Rights-based Direct Practice with Children. It starts with the methodology of participatory group workshops to facilitate learning of the content. The content draws linkages among the foundation of life skills; psychosocial, sociological and critical theories of childhood; and child rights values, categories and principles; with the approaches, methods and skills of direct practice with children. The book takes examples from India but makes significant contribution to training and reference material for child rights teachers, trainers, facilitators and field workers, across the world, especially in the developing countries.